What Roles Do Probiotics Play in the Eradication of Helicobacter pylori? Current Knowledge and Ongoing Research - Han-Yi Song; Long Zhou; Dong-yan Liu; Xin-Jie Yao; Yan Li (Gastroenterology Research and Practice)
With the rising global prevalence of antibiotic resistance, the eradication rate of Helicobacter pylori (HP) is continuing to decrease. Probiotics are beneficial to human health and may be an adjunct therapy to increase the eradication rate of HP, lower treatment-associated side effects, and reduce HP-associated gastric inflammation. However, inconsistent test results have prevented conclusions about the therapeutic prowess of probiotics for HP. The mechanisms of actions of probiotics include the production of substances that inhibit or kill HP or compete with HP for the adhesion site on gastric epithelial cells. Probiotics can also reduce the release of inflammatory factors by regulating the local immune response of the host. We searched the available literature for full-length articles focusing on the role of probiotics in HP management. This review presents the latest advances in this area.